The TELE-DD project on treatment nonadherence in the population with type 2 diabetes and comorbid depression - Juan Francisco Roy (Nature Portfolio, 2021)
Abstract Diabetic patients have increased depression rates, diminished quality of life, and higher death rates due to depression comorbidity or diabetes complications. Treatment adherence (TA) and the maintenance of an adequate and competent self-care are crucial factors to reach optimal glycaemic control and stable quality of life in these patients. In this report, we present the baseline population analyses in phase I of the TELE-DD project, a three-phased population-based study in 23 Health Centres from the Aragonian Health Service Sector II in Zaragoza, Spain. The objectives of the present report are: (1) to determine the point prevalence of T2D and clinical depression comorbidity and treatment nonadherence; (2) to test if HbA1c and LDL-C, as primary DM outcomes, are related to TA in this population; and (3) to test if these DM primary outcomes are associated with TA independently of shared risk factors for DM and depression, and patients’ health behaviours. A population of 7,271 patients with type-2 diabetes and comorbid clinical depression was investigated for inclusion. Individuals with confirmed diagnoses and drug treatment for both illnesses (n = 3340) were included in the current phase I. A point prevalence of 1.9% was found for the T2D-depression comorbidity. The prevalence of patients nonadherent to treatment for these diseases was 35.4%. Multivariate analyses confirmed that lower diabetes duration, increased yearly PCS visits, HbA1c and LDL-C levels were independently related to treatment nonadherence. These findings informed the development of a telephonic monitoring platform for treatment of nonadherence for people with diabetes and comorbid depression and further trial, cost-effectiveness, and prognostic studies (phases II and III).